2022
DOI: 10.31083/j.rcm2302064
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behavioral intentions of aortic dissection survivors towards exercise: an application of the health action process approach framework

Abstract: Background: Exercise can help patients with aortic dissection (AD) control blood pressure, prevent further progression of AD, promote mental health, improve the prognosis of cardiovascular disease, and improve their overall quality of life. However, it is not clear what the attitudes and behavioral intentions of AD survivors are towards exercise. Methods: This exploratory qualitative research was based on the Health Action Process Approach (HAPA) theory to explore the cognition, attitude, motivational factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results of EFA showed that action planning and coping planning were in the same dimension, so we combined the two into one dimension (implementation intention). In addition, in contrast from the HAPA theory, we found that social support was a very important factor for the persistence of exercise behavior in the interview process [ 19 ], so we added the dimension of social support to measure EABIQ. The modified questionnaire items were clear and easy to understand following a pilot study and formal investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of EFA showed that action planning and coping planning were in the same dimension, so we combined the two into one dimension (implementation intention). In addition, in contrast from the HAPA theory, we found that social support was a very important factor for the persistence of exercise behavior in the interview process [ 19 ], so we added the dimension of social support to measure EABIQ. The modified questionnaire items were clear and easy to understand following a pilot study and formal investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four AD patients in Wuhan, China were invited to participate in semi-structured interviews from April 2021 to June 2021 [ 19 ]. In addition, we added a dimension of perceived social support according to the semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emotional aspects significantly contribute to exercise intentions [1]. Scholars like [25] and [26] exert attitudes and behavioural intentions as robust predictors of dissection survivors towards exercise. In the perception of [27], teachers' self-efficacy, attitudes, and intentions regarding implementing a new physical education curriculum had affected students' exercise intentions.…”
Section: Intention Towards Exercise (Itwe)mentioning
confidence: 99%
“…Especially, as pointed out by Luszczynska et al ( 2011 ), action planning is unable to promote physical activity among those without strong self-efficacy. Indeed, people with low self-efficacy often lack clear action plans, thus exhibiting less exercise intention (Feng et al, 2022 ). Accordingly, high self-efficacy is positively related to planning, which further promotes health-promoting intention.…”
Section: Introductionmentioning
confidence: 99%